2014
DOI: 10.1016/j.vaccine.2013.11.099
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant antigens based on toxins A and B of Clostridium difficile that evoke a potent toxin-neutralising immune response

Abstract: HighlightsDefinition of Clostridium difficile toxin-derived antigens for soluble expression in E. coli.Demonstration of their potent neutralising immune response against key epidemic strain toxins.TcdA and TcdB were different with respect to the domains that evoke a neutralising immune response.TcdB central domains dominate the generation of a toxin-neutralising response.Generated antibodies prevent C. difficile infection in passive immunisation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In fact, the importance of the CPD in eliciting anti-TcdB neutralizing antibodies was also documented by a recent report, in which a TcdB fragment (TxB4) containing RBD and TMD only induced half the amount of anti-TcdB neutralizing antibodies when compared to another TcdB fragment (TxB5) comprised of the CPD in addition to the TMD and RBD. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the importance of the CPD in eliciting anti-TcdB neutralizing antibodies was also documented by a recent report, in which a TcdB fragment (TxB4) containing RBD and TMD only induced half the amount of anti-TcdB neutralizing antibodies when compared to another TcdB fragment (TxB5) comprised of the CPD in addition to the TMD and RBD. 45 …”
Section: Discussionmentioning
confidence: 99%
“…For example, the C‐terminal heavy chain domain of clostridial botulinum neurotoxin, a highly toxic protein that causes botulism, has been produced with BEVS and has demonstrated immunogenicity and challenge protection in mice [114, 115]. Recombinant toxin vaccines for other diseases such as Clostridium difficile could also be possible [116, 117].…”
Section: Conclusion and Future Opportunitiesmentioning
confidence: 99%
“…In our previous study ( 25 , 26 ), and consistent with others ( 27 , 28 ), we indicated that the N-terminus of TcdB was able to elicit a protective antibody response. We ( 25 ) and others ( 29 ) also indicated that CPD could play important roles in maintaining the native structure or epitope conformation of GTD. In this study, we generated a new chimeric protein, Tcd169, by fusing GT, CPD, and RBD of TcdB and RBD of TcdA.…”
Section: Introductionmentioning
confidence: 72%